EFEKTIVITAS PELAYANAN PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT DI DESA WAREMBUNGAN KECAMATAN PINELENG KABUPATEN MINAHASA - PALIT, FENSY MONICA; TAMPI, GUSTAAF BUDDY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2019)
Provision of adequate drinking water for villagers is an inseparablepart of the government's efforts to meet one of the basic human needs. Theinherent and fundamental water needs are increasing along with the increase inpopulation, moderation of life and the level of economic progress of the Pamsimascommunity is one of the mainstay programs of the government in the provision ofclean water and sanitation for rural and suburban communities throughcommunity-based approaches. The Pamsimas program began in 2008, where theimplementation has so far succeeded in increasing rural and suburban areas thatcan access drinking water and sanitation services. The program also enhances thevalue and behavior of clean and healthy living in the population of) theeffectiveness of a measure that states how far targets (quantity, quality and time)have been achieved, or the significance of the percentage of targets achieved, thehigher the effectiveness. Accuracy of program objectives, program socializationand program monitoring In this study, researchers used a type of descriptivestudy using a qualitative approach. This research approach was chosen becausethe researcher wanted to solve the problem by describing or describing thecurrent state of the object of the researcher based on the facts that exist anddescribed in the form of words and language obtained from observations,interviews and documents. Monitoring is the process of supervision or checkingprogram activities is it appropriate that is wasted and in the pamsimas program isvery wasted the monitoring process from the village government as a serviceprogram supervisor in order to be able to carry out the monitoring processpamsimas program includes actions Program Objectives Not exactly neededwater debit cannot meet the needs of the community so that the community in theprovision of water services The program has been carried out to the communityby the village government in the form of socialization within the community.Program Monitoring has been carried out by the village government throughsupervision and coordination between the government and PAMSIMASmanagement The target of the PAMSIMAS program must be expanded inaccordance with the needs of the community. Socialization of the PAMSIMASprogram is still being carried out to the community. There is a need forsupervision from the community regarding PAMSIMAS management.Keywords: Stipulation, Program, Monitoring, Socialization Target.